A Study of Research Trends in Iranian Journals of Medical Education - Meisam Dastani; Alireza Atarodi; Saeed Erfanpoor (Mashhad University of Medical Sciences, 2021)
Background: Nowadays, with the increasing number of articles in the field of medical education, the analysis of the trend of articles published in specialized journals in the field of medical education becomes important for adopting necessary measures in this field. For this purpose, the present research studies the trend of articles published in Iranian journals of medical education. Methods: A descriptive exploratory approach has been used in this study to analyze the articles published in Iranian journals of medical education from 2004 to 2018 using text mining techniques. In this study, the Python programming language and NLTK toolkit have been used for text mining. Results: The findings of this study indicated that the terms such as students, medicine, education, learning, and university are the most repetitive terms in these articles. The results of the implementation of k-means clustering algorithm have revealed that the main theme and sentence of the five thematic clusters in this study is the term "education" or "medical student education" and the subjects of the most of articles published in medical journals are in the field of education. Conclusion: The results of the present study indicated that the articles published in Iranian journals of medical education focus on general subjects of medical education such as curriculum, medical students, and teaching in the academic environment; however, other issues have been less discussed.